A coach`s political use of video-based feedback: a case study in elite-level academy soccer - Booroff, M.; Nelson, L.; Potrac, P. (Journal of Sports Sciences, 2016)
This paper examines the video-based pedagogical practices of Terry (pseudonym), a head coach of a professional junior academy squad. Data were collected through 6 in-depth, semi-structured interviews and 10 field observations of Terry`s video-based coaching in situ. Three embracing categories were generated from the data. These demonstrated that Terry`s video-based coaching was far from apolitical. Rather, Terry strategically used performance analysis technologies to help fulfil various objectives and outcomes that he understood to be expected of him within the club environment. Kelchtermans` micropolitical perspective, Callero`s work addressing role and Groom et al.`s grounded theory were primarily utilised to make sense of Terry`s perceptions and actions. The findings point to the value of developing contextually grounded understandings of coaches` uses of video-based performance analysis technology. Doing so could better prepare coaches for this aspect of their coaching practice.